My Instagram, My Portfolio: Building Visual Artist Personal Branding in Social Media - Aprilia, Monika Pretty; Kadek Kiki Astria; Yulinda Erlistyarini; Kartika Sari Yudaninggar (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2025)
The presence of social media has opened up opportunities for more Indonesian visual artists to have their works recognized internationally. However, many artists still fail to realize the importance of personal branding. In Indonesia, most artists tend to focus more on production and the creative process of making art. However, in this day and age, social media can help artists shape their personal brand, which creates a positive image that benefits the development of their careers. This research aims to examine how Indonesian visual artists develop their personal branding through their Instagram accounts. The data collection technique used in this research involves conducting in-depth interviews with 10 visual artists located in Bandung, Yogyakarta, and Denpasar. The findings reveal that these ten artists utilize Instagram to construct their portfolios. The majority of informants access Instagram daily, which positively impacts their personal brand development. These findings provide a more comprehensive reference for the case of personal branding among artists in Indonesia